Congregating behavior and response to resource distribution of the Green House Millipede, Oxidus gracilis - Bulpitt,Gregory (PeerJ Preprints, 2016)
Background. Congregating behaviors, though common among many animal species, are little studied among millipedes. It is also unclear to what extent abiotic factors influence the distribution and behavior of millipedes. The species Oxidus gracilis was surveyed around several streams on the island of Mo’orea along with soil moisture, leaf litter cover, and rock cover. Experiments were designed in order to determine how an innate congregating behavior may affect their distributions. Methods. Fifteen transects were performed in the field, recording O. gracilis abundances and the three environmental factors every 1 m. Forty trials were performed using covered bins filled with soil and five fruits of the Tahitian chestnut tree (Inocarpus fagifer). Ten millipedes were placed in the box and left for an hour, after which the number of individuals per fruit was recorded. Results. It was found that while none of the three environmental factors were strong indicators of the distribution of O. gracilis , individuals did in fact demonstrate a tendency to congregate in the experimental trials. Discussion. The lack of significant relationships with the three environmental parameters suggests a generalist behavior of this millipede species, potentially benefitting its invasive nature. The congregating behavior could potentially be for the purposes of mating or defense. Although not studied in this paper, it is possible that conspecific chemical cues are responsible.
Keywords: Congregation; Millipedes; Behavioral Ecology; Mo'orea; Tropical Rainforest